Determinants of chemical input use in periurban lowland systems: bivariate probit analysis in Cameroon - Nkamleu, G.B.; Adesina, A.A. (Elsevier, 2000)
Low use of chemical inputs has been cited as a major factor limiting productivity growth of agriculture in most of sub-Saharan Africa. A wide range of variables influence adoption of such input. It is important to understand the role of these factors to ensure the development and implementation of more effective programs to promote agricultural input use. This study examines the effect of socio-economic factors on the likelihood of using chemical fertilizer and pesticide in peri-urban lowland agricultural systems in Cameroon. Rather than the univariate probit model which is commonly used, the bivariate probit model is employed to take account of the correlation between the disturbances. Results generally indicate that lowland farmers who are more highly educated, those with temporary land rights and those whose fields are more distant from the homestead are more likely to use chemical fertilizer. In the same way, lowland male farmers, those who have contact with extension, those who have temporary land rights or those practising continuous cropping are more likely to use chemical pesticides.